The waving of the Jalur Gemilang Energizes the Closing Ceremony of the Kembara Prihatin@Bumi Kenyalang - Nor Salwana, Mohammad Idris (UMPSA, 2024)
BELAGA, 17 August 2024 – The Closing Ceremony of the Kembara Prihatin@Bumi Kenyalang 2.0 concluded with much excitement, as participants waved the Jalur Gemilang, enhancing the spirit of the National Month and Malaysia Day.